Narzędzia i techniki phishingu - Małachowski, Andrzej; Szymczak, Krzysztof (Tools and Methods of Phishing, 2007)
Phishing - the method of acquining confidential transaction data from unaware clients - has become the basic problem of safety thread in e-business. Telecommunication and teleinformation technologies may serve as platforms for phishing activities. The paper presents a review of several advanced tools and methods used in this type of cyber crime.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 29-39